Strategi peningkatan usaha kecil mitra bank wakaf mikro Fataha Kampung Maredan Barat Kecamatan Tualang Kabupaten Siak - Winario, Mohd; Yasra, Dewi; Asnawi, Mizan (STAI Auliaurrasyidin Tembilahan, 2025)
Micro Waqf Bank was established to facilitate access for low-income communities to obtain Sharia-based business financing in a fast, simple, and interest-free manner. This study aims to identify effective strategies in improving the performance of BWM partner small businesses in Maredan Barat Village. This study uses a qualitative method with a descriptive approach. Data were obtained through in-depth interviews, and observations analysis of BWM partner small business actors. SWOT analysis was used to formulate strategies for improving small businesses based on the strengths, weaknesses, opportunities, and threats faced. The results of the study indicate that the BWM program has a positive impact in the form of increased access to capital, income, and managerial skills. However, there are still obstacles in technology adoption, product diversification, and marketing network development. To overcome this, the recommended strategies include strengthening human resource capacity, utilizing digital technology, product diversification, and developing distribution networks. In conclusion, BWM Fataha plays an important role in empowering small businesses, but a more holistic and sustainable strategy is needed to improve the competitiveness of business actors at the local and regional levels.